Kwezens, Gizaagi'in - Sinclair, Minowaywayjiwan (Journal of Indigenous Social Development, 2023)
This creative non-fiction text offers a critique and self-reflection about imposed gender identities and roles, and their impacts on Indigenous ways of being and becoming.